Relationship Between Family Support and Diet Compliance in Diabetes Mellitus Patients Type 2 in Internal Disease Poly RSU Karsa Husada Batu - Chindy Surya Kencana; Achmad Dafir Firdaus; Risna Yekti Mumpuni (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Diabetes mellitus is a chronic disease which is one of the health problems in Indonesia with a prevalence of 24.49 million people. One of the management of diabetes mellitus is diet therapy. In this effort, people with diabetes mellitus need support, especially family support. The purpose of this study was to determine the relationship between family support and dietary compliance in patients with type 2 diabetes mellitus. This research method used a casual comparative research type with a cross sectional design. A sample of 34 respondents with type 2 diabetes mellitus was taken using a purposive sampling technique. The research instrument used a family support questionnaire and a type 2 diabetes mellitus diet compliance questionnaire. The data analysis method used Spearman Rank correlation. The results showed that most respondents with type 2 diabetes mellitus received family support in the very good category (67.6%) and quite well in implementing the type 2 diabetes mellitus diet (76.5%). The Spearman Rank correlation result of 0.462 means that family support is increasing, adherence to the type 2 diabetes mellitus diet will also increase, with a p value of 0.006 (p value <0.05) which means that there is a significant relationship between family support and adherence to diet. in patients with type 2 diabetes mellitus. Good family support will affect the level of dietary compliance in type 2 DM patients